How do female directors improve board governance? A mechanism based on norm changes. Issue 1 (April 2020) - Srinidhi, Bin; Sun, Ye; Zhang, Hao; Chen, Shiqiang
Abstract: Prior literature documents that corporate boards with female directors produce better governance outcomes than all-male boards. However, female directors constitute the minority on most boards, which precludes majority voting as the mechanism through which they change board decisions. We identify changing the norms of how the board works as this mechanism. Using the market for norms framework, we explain how female directors are effective even without possessing a board majority or other sources of symbolic power, such as hierarchical authority and social gravitas. Empirically, we show that independent female directors, compared to their male counterparts, are more effective at changing board norms (board processes) and improving governance (board outputs).